Compensation of MR head non-linearities using a saturable transfer function - Lin, Maria Yu (2009)
It is well known that the nonlinear behavior of Magneto-Resistive (MR) heads result in the isolated pulses having asymmetry and saturation. These nonlinear effects can be quantified by measuring the positive and negative isolated pulses. In this paper, we propose a saturable model for estimating the MR nonlinearity from read-back signals. It models the nonlinearity using bias and saturation parameters. The proposed model can be used to compensate the nonlinearity in the read-back signal, thus providing a way to linearize the channel. Simulations done using measured data demonstrate the effectiveness of the proposed model.